Commemoration of the 25th anniversary of the foundation of the Society of Surgery of Uruguay - Soto Blanco, Juan (Cirugía del Uruguay, 2020)
Presented at session November 1945. It includes speeches of Armando Loubejac, Carlos Stajano, Fernando Etchegorry